AI’S TRANSFORMATIVE POWER IN MASTERING LANGUAGES - Khodjakulova Feruza Rustamovna (Web of Journals Publishing, 2025)
Artificial intelligence is transforming language learning—accelerating it, personalizing it, and adding fun. This article synthesizes 52 studies from 2019–2025, highlighting AI's strengths in vocabulary building, pronunciation correction, conversation practice, and writing assessment. Learners recall 28–35% more words and reduce pronunciation errors by 40%. However, AI lacks humor, cultural nuances, and empathy. We advocate a balanced method: use AI for repetition and feedback, but prioritize teachers and authentic conversations. When implemented well, AI can provide quality language education to millions previously without access.
Keywords: AI, language learning, machine learning, speech recognition, chatbots, personalized learning, pronunciation, vocabulary, culture, teaching.